THE RETURN - Fox, Linda Andrea (East Carolina University, 2012)
"The Return" investigates how culture shapes our understanding of the natural world. The life process of death is the key to this understanding. Culture has interpreted, compartmentalized, or rationalized this process in such a way as to prevent a holistic relationship with the earth and with ourselves.   Creative processes in which we work -- painting, literature, and photography -- are not that dissimilar to the creative life processes in which we are immersed and those that surround us. Death as a creative process is a necessary step toward regeneration and renewal. I approach my photographic subjects with the understanding that these images of what I am seeing are also in the midst of a creative process.  I utilized the method of series or sequence - to hold the moment in the death-life process, a moment that needed to be suspended, so one could look at it with more than one glance, have the time to look into time and change, to study its movement and its confusion and beauty - so that the effect of an image captured in a series on the observer would hold a more lasting, fluid impression.  I photograph common animals encountered in ordinary small town life; animals one might see by the side of the road, a domesticated dog killed by a car, a neighborhood cat, a discarded catfish caught in a nearby river and left behind, a mourning dove that has broken its neck, a deer in season killed by local hunters, a feral fox killed on the highway. These subjects are currently part of a human being's conscious and unconscious awareness of the animal world in a typical small town. They may be a part but not a necessary part of the human world (excluding the emotional relationship between pet owner and pet); that is, they are elements of the world viewed from an unaffected distance.  "The Return" recognizes the possibility to recreate visions of the natural world that are more harmonious and less compartmentalized, more wholesome, less segmented, and avoid the segregation of "diseased" versus "healthy," "polluted" versus "unpolluted," or "dead" versus "living," In some small way, I am aiming to encourage a view of the natural world that sees value and beauty in all of its processes.
Keywords: Fine arts; Death in art; Biodegradation; Photography